Influence of mass media on english learners’ academic development. Case of English IV students of the Economic Sciences School, at the University of El Salvador, second semester of the year 2015 - Rodríguez Orellana, Mauricio Alberto (2024)
When an individual is stating that he or she is starting to study a target language, a common advice comes in the popular wisdom: Use the Mass Media. Some segments of the general public in the target language have been saying that the Mass Media are a detriment to the language gaining. This is treated mostly in the learning of the mother tongue as noted by Aitchinson et al. (Language Myths, 2005) but not much work has been done in a place where the target language is a foreign language. The cost of equipment is going down, which makes it easier for students to buy or acquire some equipment such as laptops or very powerful cell phones. And thanks to the actual coverage of telecommunications the capacity to get online and consult for something is incredibly easier as well. This translates into the capacity to get authentic materials at a whim. One of the most constant mentions when dealing with Mass Media and one that several individuals will take around Wertham’s idea that some aspects of Mass Media are detrimental to the learning and wellbeing of the individual. Most of those negative mentions are around the areas of graphic novels, comics and video games. Aitchinson (2005) mentions that the notion of Mass Media being sloppy is a perception had by several individuals; it is not a new complaint as the ball has been passed by several groups for years. However, Van Eck et al. (2005) mention that the use of serious games can deal to substantial learning. Which is the actual coverage of the Mass Media in the individuals? What are the consumption habits in the students? How much of it appears in the grammar skills and understanding of them? These are several questions that this study seeks to answer. This thesis is made up of the following chapters: Research questions – general and specific – which generate the corresponding objectives. Next part is justification, which highlights the importance of this research. The theoretical framework follows this document by presenting different sources and points of view. Methodology comes next, which refers to the different procedures followed by the researcher. Afterwards appears Data Analysis and Interpretation chapter, which shows the findings obtained in the research. Conclusions and Recommendations are presented later. Finally, the researcher includes the references consulted and the appendices, which contain information on the research procedure. Influence of Mass Media on English Learners’ Academic Development. Case of English IV Students of the Economic Sciences School, at the University of El Salvador, Second Semester of the Year 2015